The Mediated Learning Experience Method On The Quality of Interaction Between Mothers and Children - Fitriani Dzulfadhilah; Sri Rika Amriani; Angri Lismayani; Rika Kurnia R; Parwoto Parwoto (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
This study aims to determine the effect of applying the Mediated Learning Experience (MLE) method on mothers with children aged 5-6 years to improve the quality of interaction in learning assistance activities. The research approach used was quantitative with pre-experimental types. The research design used was single-group, pretest-posttest. The population of this study was all students at Nadira Kindergarten, Takalar Regency. The sampling technique used was purposive sampling, so the subjects in this study were seven children aged 5-6 years. The data collection technique used in this study was the NST questionnaire, interviews, and Mediated Learning Experience Rating Scale (MLERS) instrument. The methods used are descriptive statistical analysis and nonparametric statistical analysis using the Wilcoxon test. The results of hypothesis testing using the SPSS application show that the data Asymp (2-tailed) = 0.018 <0.05, then Ha is accepted, and H0 is rejected. The results showed an effect of applying the Mediated Learning Experience (MLE) method on the quality of interaction between mothers and children aged 5-6 years in learning assistance activities